2008
DOI: 10.1111/j.1749-7345.2008.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Survival of Cobia, Rachycentron canadum, during Simulated Transport

Abstract: Interest in cobia, Rachycentron canadum, culture has shown significant growth in recent years, but few hatcheries are available to support this developing industry. To facilitate the transport of cobia between facilities, four 24‐h experiments were conducted to examine the effects of density, temperature, and actual versus simulated transport on juvenile cobia (1.5–3.0 g) survival. Mortality during actual transport at fish densities of 5, 10, and 15 kg/m3 (2.9 ± 0.6, 2.9 ± 1.8, and 6.3 ± 0.8%, respectively) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Temperature and salinity were maintained at 20 1C and 32 ppt respectively. Fish density during transport was 2 g L À 1 , below the limit of 20 g L À 1 recommended by Colburn, Walker, Berlinsky and Nardi (2008).…”
mentioning
confidence: 70%
“…Temperature and salinity were maintained at 20 1C and 32 ppt respectively. Fish density during transport was 2 g L À 1 , below the limit of 20 g L À 1 recommended by Colburn, Walker, Berlinsky and Nardi (2008).…”
mentioning
confidence: 70%
“…Water conditioners like the one used in this study (i.e. Trizma â ) have been used safely and effectively to buffer against changes in pH for both fresh and salt water species in concentrations as high as 3.0 g L À1 (Piper, McElwain, Orme, McCraren, Fowler & Leonard 1982;Turner & Bower 1982;FAO 1986;Colburn et al 2008). In both CYT and WSB trials, pH levels dropped below 8.0 when the buffer concentrations were below 1.5 g L À1 and when stocking densities were increased above 6000 larvae L À1 .…”
Section: Discussionmentioning
confidence: 99%
“…; Estudillo & Duray ), cobia (juvenile; Rachycentron canadum ; Colburn et al . ) and yellowfin tuna (yolk‐sac larvae; Thunnus albacares ; Zink et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress Coat â (API Aquarium Pharmaceuticals Inc., n.d.) is a commercially available water conditioner which is recommended for addition to water during transport and to tank water during other potentially stressful procedures. Several studies have used Stress Coat â in husbandry procedures (Earley et al 2006;Colburn et al 2008;Harnish et al 2011;Wong et al 2015), however, much of the information on Stress Coat â is not in the peer-reviewed literature. Snellgrove et al (2007) found that water cortisol levels excreted by goldfish exposed to Stress Coat â were lower following netting compared with goldfish netted with no Stress Coat â exposure.…”
Section: Maintaining Mucus Integritymentioning
confidence: 99%